N-Methyl-D-Aspartate (NMDA) Receptors in the Prelimbic Cortex Are Required for Short- and Long-Term Memory Formation in Trace Fear Conditioning - Eui-Ho Park; Nam-Soo Kim; Yeon-Kyung Lee; June-Seek Choi (Life, 2022)
Accumulating evidence suggests that the medial prefrontal cortex (mPFC) has been implicated in the acquisition of fear memory during trace fear conditioning in which a conditional stimulus (CS) is paired with an aversive unconditional stimulus (UCS) separated by a temporal gap (trace interval, TI). However, little is known about the role of the prefrontal cortex for short- and long-term trace fear memory formation. Thus, we investigated how the prelimbic (PL) subregion within mPFC in rats contributes to short- and long-term trace fear memory formation using electrolytic lesions and d,l,-2-amino-5-phosphonovaleric acid (APV), an N-methyl-D-aspartate receptor (NMDAR) antagonist infusions into PL. In experiment 1, pre-conditioning lesions of PL impaired freezing to the CS as well as TI during the acquisition and retrieval sessions, indicating that PL is critically involved in trace fear memory formation. In experiment 2, temporary blockade of NMDA receptors in PL impaired the acquisition, but not the expression of short- and long-term trace fear memory. In addition, the inactivation of NMDAR in PL had little effect on locomotor activity, pre-pulse inhibition (PPI), or shock sensitivity. Taken together, these results suggest that NMDA receptor-mediated neurotransmission in PL is required for the acquisition of trace fear memory.